THE POSITION AND PROTECTION OF CONCURRENT CREDITORS IN INDONESIA’S BANKRUPTCY PROCESS: A REVIEW BASED ON THE PRINCIPLE OF CREDITORIUM PARITY - Lira, M. Adnan (The Juris, 2024)
This research aims to analyze the position and protection of concurrent creditors in Indonesia, particularly in the context of Decision Number 113/Pdt.Sus-PKPU/2019/PN.Niaga.Jkt.Pst. Using normative research methods, this study examines primary, secondary, and tertiary legal materials to address challenges faced by concurrent creditors in bankruptcy proceedings. The findings highlight the implementation issues of creditorium parity and provide recommendations for enhancing the legal framework. The research process involves inventory and identification of relevant legal materials, including primary, secondary, and tertiary sources. The stages of processing include the systematic collection and examination of these sources to analyze issues related to concurrent creditors in bankruptcy cases. Through an analysis of statutory provisions, court decisions, and practical bankruptcy procedures, this research reveals that while the principle of creditorium parity aims to ensure fair and balanced treatment among creditors, its implementation faces significant challenges. These challenges include differences in the positions of concurrent creditors, separatist creditors, and preferred creditors, as well as the complexities and bureaucratic nature of the bankruptcy process, which often hinder concurrent creditors from obtaining their rights.Court decisions, such as Decision Number 113/Pdt.Sus-PKPU/2019/PN.Niaga.Jkt.Pst., demonstrate that the position of concurrent creditors is protected under Articles 1131 and 1132 of the Civil Code. This decision confirms that concurrent creditors have equal rights in creditor meetings, based on the amount of their claims.